Migration, gender, and emotions: A reflection on global care chains and circuits of care in the context of migration from Bolivia to Argentina - Blanco Rodriguez, Guadalupe (2023)
The intersection between the history of emotions and migration studies highlights how motherhood and care practices are transformed during migration. In this article, through the example of Bolivian migration to Argentina, we shed light on diverse emotional experiences around care work that cannot be understood if we analyze them through the classic approaches of global care chains and the circulation of care. In this study, we set out to analyze care practices and the emotional dynamics that are connected to them from a situated perspective that focuses on different geographic locations to those studied in these two classic approaches. We call into question essentialist views of motherhood, care, and emotions by conducting a historical analysis of human mobility between two countries in the Global South: the waves of migration from Bolivia to Argentina that took place between the 1970s and 1990s.